Revisiting the Past and Selecting for the Future: An Introduction to Handbook of Organizational Performance: Foundations and Advances. Issue 3 (3rd July 2022) - Johnson, Douglas A.; Johnson, C. Merle
ABSTRACT: Both business and behavior can be understood through the lens of variation and selection, with adaptive approaches prospering and other approaches perishing. The Handbook of Organizational Performance: Foundations and Advances series seeks to lay out the groundwork and direction for our field to prosper, as understood by many expert contributors in the field of organizational behavior management. Other worthwhile directions beyond the series are also noted, all guided by the notion that a science of behavior is not only possible, but also a critical missing component from the typical understanding of how to best operate a business so that it survives.